GENDER'S ROLE IN FINANCIAL MANAGEMENT AND PURCHASING DECISIONS ON THE QUALITY OF DUAL-EARNER FAMILY MARRIAGE DURING THE COVID-19 PANDEMIC - Cut Michelle Lazuardi; Herien Puspitawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
The misalignment of gender roles can affect the quality of marriage because it causes conditions of injustice, and one of the parties will be harmed. This study aims to determine the effect of gender roles in financial management and purchasing decisions on the quality of family marriages during the Covid-19 pandemic. A cross-sectional study design was used in the study. The method used is self-management with an online questionnaire. The study was conducted in DKI Jakarta, which was selected purposively. The voluntary sampling technique was used to obtain 106 working wives who have children and are domiciled in DKI Jakarta. The collected data were processed using Microsoft Office Excel software, Statistical Package for Social Science (SPSS) 25.0 for windows, and Smart Partial Least Square (SmartPLS). The results showed that the amount of education and income of husbands, children, family size, and gender roles in financial management and purchasing decisions were related to marriage quality. Furthermore, the regression test results show that the husband's income and gender roles in purchasing decisions positively affect the quality of marriage. This study suggests that families further improve the distribution of balanced roles in financial management activities and strategies to improve role performance.